RESEARCH OF THE ISSUE IMPROVEMENT OF THE SYSTEM OF DELIVERY OF GOODS IN INTERNATIONAL TRAFFIC AT MOTOR TRANSPORT ENTERPRISES - , С. В., К. С. (Municipal economy of cities. Series: «Economy science», 2018)
The study presents a methodology on the basis of which it is possible to compare different options for the delivery of goods in international traffic. The proposed methodology includes the implementation of a number of stages and calculation of the total costs for the delivery of goods on the developed model. The proposed model compares alternative routes, which take into account the costs of transporting goods, costs, immobilization and storage. The main source of information for calculations is the speed of movement of vehicles across the territory of Ukraine and the territory of other countries, the time of movement through the territory of Ukraine and other countries, as well as the number of border crossing points. The results of the comparison of alternative routes in the international traffic between Kiev and Shymkent are presented. Comparison and choice of routes at the enterprise was carried out among three alternative options. Keywords: transportation, cargo transportation, delivery system, international transportation, cargo.